Analisis Peramalan Permintaan dan Perencanaan Bahan Baku untuk Pengemasan Minyak Goreng - Puspita, Sesaria Mardhiani Rachma; Tatiana, Yana; Jonathan, Jonathan; Parlindungan, Purbanuara; Rahfi, Muhamad Sauqi; Aradena, Athallah Aqil Ghani Halim (Institut Transportasi dan Logistik Trisakti, 2021)
One of the manufacturing companies engaged in agribusiness, one of which is processing cooking oil, often occurs damage to goods due to excess stock of goods and increases expenses for storage costs. Before carrying out the production process, the company must forecast demand to find out how much the estimated raw material needs will be used as inventory control so that there is no excess or shortage of stock that will harm the company. The purpose of this study is to predict the amount of cooking oil demand in the next 12 periods, plan the lot size of raw materials with the lowest cost and determine the right time to order raw material supplies. The method used in forecasting is Autoregressive Integrated Moving Average (ARIMA) and lot size planning with Materials Requirements Planning (MRP) FOQ and POQ techniques. ARIMA forecasting results with a MAPE value of 33% and the lowest cost technique chosen by POQ